Pidgins and Creoles in Asia - Ansaldo, Umberto (John Benjamins Publishing Company, 2012)
Shifts the focus of Pidgin and Creole Studies from the better-known Atlantic/Caribbean contexts to the Indian Ocean, the South China Sea and Mongolia. Looking at Asian contexts before and after Western colonial expansion, this title offers readers insights into language contact in historical settings.